2012
DOI: 10.1002/gcc.22022
|View full text |Cite
|
Sign up to set email alerts
|

The human sulfatase 2 inhibitor 2,4‐disulfonylphenyl‐tert‐butylnitrone (OKN‐007) has an antitumor effect in hepatocellular carcinoma mediated via suppression of TGFB1/SMAD2 and Hedgehog/GLI1 signaling

Abstract: Human sulfatase 2 (SULF2) functions as an oncoprotein in hepatocellular carcinoma (HCC) development by promoting tumor growth and metastasis via enhancement of fibroblast growth factor-2/extracellular signal-regulated kinase and WNT/ β-catenin signaling. Recent results implicate that SULF2 activates the transforming growth factor beta (TGFB) and Hedgehog/GLI1 pathways in HCC. OKN-007 is a novel phenyl–sulfonyl compound that inhibits the enzymatic activity of SULF2. To investigate the antitumor effect of OKN-00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 34 publications
4
52
0
Order By: Relevance
“…Among this short list of 13 genes were Wwp2, S100A4, Sulf2, and Inhbb, previously reported to enhance TGFb/Activin signaling ( Fig. 6A; Matsuura et al 2010;Soond and Chantry 2011;Zheng et al 2013). qRT-PCR on independently purified HF-SCs confirmed that their mRNAs were downregulated in cKO HF-SCs (Fig.…”
Section: Sox9 Is a Positive Regulator Of Genes Involved In Activin/tgmentioning
confidence: 63%
“…Among this short list of 13 genes were Wwp2, S100A4, Sulf2, and Inhbb, previously reported to enhance TGFb/Activin signaling ( Fig. 6A; Matsuura et al 2010;Soond and Chantry 2011;Zheng et al 2013). qRT-PCR on independently purified HF-SCs confirmed that their mRNAs were downregulated in cKO HF-SCs (Fig.…”
Section: Sox9 Is a Positive Regulator Of Genes Involved In Activin/tgmentioning
confidence: 63%
“…The role of SULF2, another sulfatase enzyme, as a tumor promoter has already been established, [21][22][23] and more recently Zheng et al have shown that the TGF-b pathway can be activated by SULF2. 24 We explored the role of SULF2 in TGF-b-mediated EMT using in vitro studies and found that it had similar actions as SULF1.…”
Section: Discussionmentioning
confidence: 99%
“…From these studies we concluded that OKN-007 has the ability to cause glioma regression in aggressive rodent tumor models (F98 and U87), as well as in moderate gliomas (C6) [810]. Support for the anticancer effect of OKN-007 via the transforming growth factor β1 (TGFβ1) pathway was reported by Zheng et al, where they found that OKN-007 mediates its antitumor effect in hepatocellular carcinoma cells (Huh7) via the suppression of TGFβ1/SMAD2 and Hedgehog/GLI1 signaling by inhibiting sulfatase 2 (SULF2) enzymatic activity [59]. …”
Section: Discussionmentioning
confidence: 99%